First PET Imaging Studies With Zn-Zinc Citrate in Healthy Human Participants and Patients With Alzheimer Disease - Timothy R. DeGrado PhD; Bradley J. Kemp PhD; Mukesh K. Pandey PhD; Huailei Jiang PhD; Tina M. Gunderson MS; Logan R. Linscheid CNMT; Allison R. Woodwick CNMT; Daniel M. McConnell CNMT; Joel G. Fletcher MD; Geoffrey B. Johnson MD, PhD; Ronald C. Petersen MD, PhD; David S. Knopman MD; et al. (Molecular Imaging)
Abnormalities in zinc homeostasis are indicated in many human diseases, including Alzheimer disease (AD). 63 Zn-zinc citrate was developed as a positron emission tomography (PET) imaging probe of zinc transport and used in a first-in-human study in 6 healthy elderly individuals and 6 patients with clinically confirmed AD. Dynamic PET imaging of the brain was performed for 30 minutes following intravenous administration of 63 Zn-zinc citrate (∼330 MBq). Subsequently, body PET images were acquired. Urine and venous blood were analyzed to give information on urinary excretion and pharmacokinetics. Regional cerebral 63 Zn clearances were compared with 11 C-Pittsburgh Compound B ( 11 C-PiB) and 18 F-fluorodeoxyglucose ( 18 F-FDG) imaging data. 63 Zn-zinc citrate was well tolerated in human participants with no adverse events monitored. Tissues of highest uptake were liver, pancreas, and kidney, with moderate uptake being seen in intestines, prostate (in males), thyroid, spleen, stomach, pituitary, and salivary glands. Moderate brain uptake was observed, and regional dependencies were observed in 63 Zn clearance kinetics in relationship with regions of high amyloid-β plaque burden ( 11 C-PiB) and 18 F-FDG hypometabolism. In conclusion, zinc transport was successfully imaged in human participants using the PET probe 63 Zn-zinc citrate. Primary sites of uptake in the digestive system accent the role of zinc in gastrointestinal function. Preliminary information on zinc kinetics in patients with AD evidenced regional differences in clearance rates in correspondence with regional amyloid-β pathology, warranting further imaging studies of zinc homeostasis in patients with AD.